Strategy for Increasing the Use of Domestic Products in the Procurement of Goods/Services in Government Procurement Agency - Juniarty Erika Magdalena Saragi; Hamka Hamka; Mala Sondang Silitonga (International Journal of Economics Development Research (IJEDR), 2023)
This study aims to identify factors that influence the use of Domestic Products (PDN) in the implementation of Goods/Services Procurement (PBJ) at the Government Procurement Policy Institute (LKPP) and formulate effective strategies in increasing the use of PDN in the implementation of PBJ in LKPP. This research is qualitative research, using primary and secondary data sources with data collection techniques in the form of interviews with key informants and documentation studies. The results showed that the factors influencing the use of PDN in PBJ in LKPP include driving factors and inhibiting factors. The driving factors that influence the use of PDN in PBJ in LKPP include PDN Policy, Contract Process, Strict Procurement and Supervision Practices, and the Use of IT and PDN Information that is easily accessible. The inhibiting factors that affect the use of PDN in PBJ in LKPP include the uneven ability of PBJ human resources, the unavailability of PDN Goods/Services or their substitutions, and the quality of PDN Goods/Services is not optimal, including security system issues. This study recommends steps as a strategy to increase PDN in PBJ in LKPP, namely Internalization of PDN Policy, Optimization of PBJ Process starting from the Procurement Planning stage, Election Preparation, Election Implementation, and Preparation and Improvement of Documents ranging from Planning Documents, Election Preparation Documents and Election Implementation Documents in order to ensure PDN obligations in the implementation of PBJ.